Letter to Jane Tolmach from Arla Crane, KVEN News - Arla Crane:::::: (1976)
In a May 18, 1976 letter, Arla Crane of KVEN Radio informed Jane Tolmach that the station was arranging campaign interviews to clarify candidates' positions. The interview would address questions about Governor Brown's "lowered expectations" and county tax burdens, refinancing the Agricultural Labor Relations Board, and whether schools should be funded through local property taxes. The letter included additional guidance from the station's News Director regarding the format and presentation. Crane requested to schedule Tolmach's interview later that week.